A Preliminary Guideline for the Assignment of Methicillin-Resistant Staphylococcus aureus to a Canadian Pulsed-Field Gel Electrophoresis Epidemic Type Using spa Typing - George R Golding; Jennifer L Campbell; Dave J Spreitzer; Joe Veyhl; Kathy Surynicz; Andrew Simor; Michael R Mulvey; Canadian Nosocomial Infection Surveillance Program (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Increasing rates of methicillin-resistant Staphylococcus aureus (MRSA) infections on a global scale is a major health concern. In Canada, there are 10 known epidemic types of MRSA as determined by pulsed-field gel electrophoresis (PFGE). Despite the excellent discriminatory power of PFGE, there are several disadvantages of using this technique, such as high degree of labour intensity and the inability to easily develop an MRSA typing database due to the subjective interpretation of results.